2017
DOI: 10.5123/s1679-49742017000400013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da implantação do Programa de Controle da Hanseníase em Camaragibe, Pernambuco*

Abstract: the level of implementation found was related to the organization of services, with negative repercussions regarding the result indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 0 publications
4
10
0
12
Order By: Relevance
“…3,19,20 A study conducted in the municipality of São José do Rio Preto, SP, with the aim of assessing health services as to early detection of leprosy, revealed that people with the disease traveled 9.2km on average between their homes and the places where they got treatment, confirming the importance of decentralization for improving access, early diagnosis and treatment follow-up. 20,21 A study conducted with the aim of characterizing the flow of people with leprosy from their municipality of resident to the municipality where they got treatment, in the states of Maranhão, Pará, Tocantins and Piauí, identified gaps in this process of decentralization. Standing out, in particular, are difficulties and challenges in follow-up during and after multidrug therapy (MDT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,19,20 A study conducted in the municipality of São José do Rio Preto, SP, with the aim of assessing health services as to early detection of leprosy, revealed that people with the disease traveled 9.2km on average between their homes and the places where they got treatment, confirming the importance of decentralization for improving access, early diagnosis and treatment follow-up. 20,21 A study conducted with the aim of characterizing the flow of people with leprosy from their municipality of resident to the municipality where they got treatment, in the states of Maranhão, Pará, Tocantins and Piauí, identified gaps in this process of decentralization. Standing out, in particular, are difficulties and challenges in follow-up during and after multidrug therapy (MDT).…”
Section: Discussionmentioning
confidence: 99%
“…23 There are therefore complex challenges to be overcome by primary healthcare professionals with regard to scaling up user access to health services. 20,21 Certain issues standout among these challenges: (i) health management quality in relation to regionalized networks; (ii) continuing education for health professionals; (iii) lack of empowerment of affected people and their families Reagan Nzundu Boigny et al with regard to their right to health; and (iv) insufficiency of systematic analyses in relation to epidemiological and operational indicators in the territories. 3,8,14 The high percentages of CPCs not approached adequately at the time the ICs were diagnosed, when they were contacts, illustrate real difficulties for timely diagnosis and contact follow-up, as well as for immunoprophylaxis, these being measures that have been made known for a very long time in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Organization of services is directly correlated with the process of healing and with the improvement of quality of life. In these studies, the factors that influenced risk of illness included a lack of adequate structure, scarce resources, absence of reference service, low autonomy and management resolution, fragility in the information system, precariousness of epidemiological surveillance and educational activities, and low articulation of partnerships with social actors and institutions [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 51 documents met the inclusion criteria (Fig 1). This included 23 articles published in scientific journals [1,8,9,11,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], 3 postgraduate studies sensu stricto [3,4,10], 6 protocols, manuals, or books published by the MoH and WHO [18][19][20][42][43][44], 1 epidemiological bulletin [45], 13 laws [17,[46][47][48][49][50][51][52][53][54][55][56][57], data from 2 databases of the MoH [58,59], and content from 3 internet sites with the domain ".org"…”
Section: Methodsmentioning
confidence: 99%
“…The methodological constructs of some research studies have presented strategies to evaluate and analyze implantation of health policies and programs. At different extents, they seek to select dimensions, sub-dimensions, and criteria related to the different domains of health care models, with particular attention to management, assistance, and effectiveness of the practices based on the understanding of the programs' theory/logic model (16,17) .…”
Section: Introductionmentioning
confidence: 99%